Long Noncoding RNA SCIRT Promotes HUVEC Angiogenesis via Stabilizing VEGFA mRNA Induced by Hypoxia. (3rd June 2022) - Gao, Lianze; Yang, Jihong; Li, Yi; Liu, Keyu; Sun, Huilin; Tang, Jing; Xia, Zhengyuan; Zhang, Liangqing; Hu, Zhe
Abstract : Ischemia-reperfusion injury (IRI) is closely associated the abnormal expression of long noncoding RNAs (lncRNAs), especially for their regulatory roles in IRI-related angiogenesis. This study applied a hypoxia-reoxygenation (HR) cell model to simulate the IRI condition, as well as RNA sequencing and RNA pull-down experiments to reveal roles of the lncRNA and Stem Cell Inhibitory RNA Transcript (SCIRT), in endothelial angiogenesis. We found that SCIRT was increased under the HR condition and exhibited a high expression correlation with angiogenesis marker VEGFA. RNA-seq data analysis further revealed that VEGFA-related angiogenesis was regulated by SCIRT in HUVECs. Gain and loss of function experiments proved that SCIRT posttranscriptionally regulated VEGFA via affecting its mRNA stability. Furthermore, HuR (ELAVL1), an RNA binding protein (RBP), was identified as a SCIRT-binding partner, which bound and stabilized VEGFA. Moreover, SCIRT promoted HuR expression posttranslationally by inhibiting its ubiquitination under the HR condition. These findings reveal that lncRNA SCIRT can mediate endothelial angiogenesis by stabilizing the VEGFA mRNA via modulating RBP HuR stability under the HR condition.